(untitled) (Asian Journal of Social Science Studies, 2022)
Chengdu Traditional Chinese Medicine College is one of the first four TCM colleges in the People‘s Republic of China founded in 1956. The central government made the establishment decision and Chengdu face the southwest of China to enroll. The College‘s training objectives, educational system, and student number were all uniformly stipulated by the top. The College planned to train senior practitioners with Marxist and Leninist ideas and mastery of Chinese medicine academic knowledge and medical technology for Socialist Construction and people‘s healthcare. The founding of the Chengdu College of TCM is on the track of modern Chinese medical history. Chinese medicine has become an issue to debate since modern times, in the face of the abolition crisis and scientific discussions, Chinese medicine education is learning from the West to promote. The close connection between traditional medicine and the mass reflects its cultural connotation. The rehabilitation of Chinese medicine as a medical discipline is inseparable from the ruling party‘s support. Chinese medicine is a tool to consolidate the regime of the Chinese Communist Party. Founding the TCM colleges is beneficial for training many practitioners to serve the state power.